Effect Of Keren Fruit Extract (Muntingia calabura) On Blood Glucose Levels Of Rats (Rattus novergicus) Which Induced By Streptozotocin (STZ) - Vembriarto Jati Pramono; Rahmad Santosa (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2014)
Diabetes mellitus is reveal various symptoms that characterized by increasies of blood glucose levels (hyperglycemia) due to insulin deficiency. Kersen fruit (Muntingia calabura) is thought to contain antidiabetic substance such as ascorbic acid, fiber, beta-carotene, riboflavin, thiamine and niacin. The study was conducted to determine the potential of kersen fruit in decreasies blood sugar levels. The group divided into group I (negativecontrol), group II (positive control), group III, IV, and V were given kersen fruit extract 100 mg/kg BW, 200 mg/kg BW, and 400 mg/kg BW respectively. Rats of groups I-V were induced with streptozotocin (STZ). Blood sugar values were analyzed using Analysis of Variance Repeated method (Repated ANOVA). The results showed blood glucose levels before treatment, week-0, and week-2 in the group I (133 mg/dL, 164 mg/dL, 105 mg/dL), group II (136 mg/dL, 362 mg/dL, 431 mg/dL), group III (133 mg/dL, 513 mg/dL, 109 mg/dL), group IV (100 mg/dL, 376 mg/dL, 153 mg/dL), and group V (83 mg/dL, 225 mg/dL, 169 mg/dL). Respectively based on statistical analysis showed a significant decreasies of blood sugar levels of the group III so that kersen extract with the dose of 100 mg / kg has the potential to antidiabetic.